Laporan Keuangan Masjid Berdasarkan ISAK Nomor 35 dan PSAK Nomor 109: Studi Kasus Mesjid Al Ikhlas Banjarmasin - Hasdi Suryadi; Abul Hasan Asy’ari; Yudi Rahman; Fauziannor Fauziannor; Imawati Yousida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
his study aims to analyze the financial recording and reporting practices of Al Ikhlas Mosque in Banjarmasin and compare them with the accounting standards that should be applied, namely ISAK 35 on Financial Reporting for Nonprofit Entities and PSAK 109 on Accounting for Zakat, Infaq, and Sadaqah. The research employs a descriptive qualitative approach using primary data obtained through interviews with the mosque’s chairman and treasurer, and secondary data from the 2025 financial records. The findings indicate that the mosque uses a simple cash-in and cash-out recording system without proper fund classification or separation aligned with accounting standards. The mosque has not prepared a statement of financial position, statement of comprehensive income, statement of changes in net assets, cash flow statement, nor notes to the financial statements as required under ISAK 35. Additionally, the mosque has not implemented the required separation of zakat, infaq/sadaqah, and waqf funds in accordance with PSAK 109. The main contributing factors include limited accounting competence among mosque administrators and low awareness regarding the importance of financial transparency and public accountability. This study provides an illustrative model of compliant financial statements based on ISAK 35 and PSAK 109, which can serve as a practical reference to improve accountability and build trust among congregants.